Converture; Space-Saving Furniture Design With Conversion Concept Through Knock-Down System - Amanda Rosetia; Leonardo Leonardo; Devi Fevita; Novya Mardhika; Delny Delny (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Nowadays, more residential buildings are built with small interior spaces, but the average size of the furniture remains constant; large enough. This can trigger such problems like limited area of a space, so it could restrict some activities of users of that space. The purpose of this research is to create a furniture with the concept of convertible furniture to overcome these problems. This study also focuses on business opportunities that apply convertible furniture sales with the unique concept of using used or recycled materials. The method used in this research is a qualitative research method and a descriptive method accompanied by the distribution of questionnaires to collect empirical data as part of the qualitative research method. The results of the study concluded that furniture with ‘convertible furniture’ concept through knock-down technique may solve the problem of limited space, and has the potential to grow a ‘convertible furniture’ business with some portion of the materials containing recycled material(s).